Analysis of Budget Utilization for Public Health Efforts at Puskesmas X in Medan City - Hasibuan, Indah Doanita; Br Barus, Maharani; Lubis, Putri Ananda; Silalahi, Suhayla Azhari; Annisa, Frety Salma (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Population growth results in a larger health budget. A health budget is a funding plan created to promote public health. The central government is the source of the health budget through the Deconcentration Fund which comes from the State Budget. This study aims to determine the utilization of the Public Health Efforts budget at Puskesmas X in Medan City. The type of research used is qualitative research with a case study approach. Data analysis techniques using descriptive analysis. Data collection was carried out using observation techniques, documentation and in-depth interviews with informants who manage the health budget. The research informants were the head of the puskesmas, the treasurer, the head of the program implementer, the head of the administrative subdivision and the person in charge of the Community Health Efforts program. Selection of informants using purposive sampling, namely the sample is determined by certain considerations. The results of the study revealed that the utilization of the Community Health Efforts budget of Puskesmas X Medan City has been running in accordance with the provisions. Target accuracy is families, groups and communities help achieve better health development goals.